The inheritance distribution system for daughters of the Karo Patumbak community in Kampung, Deli Serdang Regency - Nasution, Maisyarah; Ja’Far, Hasbullah (Trigin Publisher, 2025)
The purpose of this study was to determine the factors behind Karo women not receiving inheritance, as well as the inheritance distribution system of the Karo Patumbak Village community in Deli Serdang Regency. The research method used in this study used qualitative research, namely a method of analyzing research results that produce descriptive analytical data, namely data obtained both in writing, verbally, and real actions that are researched and also studied as a whole. By using an empirical approach, namely the existence of field data as the main data source, such as interview results and observations. The results of this study indicate that there is an awareness in the Karo community to give their inheritance to daughters by bequeathing or granting. It is appropriate that the distribution of inheritance in the Karo community is carried out equally for men and women, or in a family way without any discrimination against women.